Digitalization and Performance of Service Sector - Gbenga, Lawal Suleiman; Ubi, Bassey Bassey; Phobuh, Chenui Armand; Obiora, Eze Prince; Meyengue, Tabi; Eventus, Bernard Samuel; Udo, Ndatah Emem (Law and Economy, 2025)
The study examined the effect of digitalization and performance of the service sector. The specific objectives were to: examine the effect of internet adoption in performance of service sector in Calabar; investigate the effect of social networking websites adoption performance of service sector in Calabar; and to ascertain the effect of mobile technology performance of service sector in Calabar. The study adopted descriptive research design. Data for this study were gathered from primary sources. The study employed multiple regression statistical tools to analyze the effect of independent variables on dependent variable. The major findings of the study include: Internet has a positive effect on performance of service sector. Social networking websites have a positive effect on performance of service sector. Mobile technology has a positive effect on performance of service sector. The study recommended that organizations should focus on training networking for employees so that they will produce best result in order to make decision in future.